Palliative care and nursing to the patient in an intensive care unit: An integrative review (Research, Society and Development, 2021)
The intensive care unit (ICU) is defined by the set of functionally grouped elements, which is intended for the care of critically ill and/or at-risk patients who need medical care, nursing and physiotherapists continuously, in addition to modern technological equipment and specialized human resources of several professionals focused on health. In order to centralize the care applied to the patient, the nursing professional who works in intensive care is challenged by the specificities of this assistance to each patient, respecting their uniqueness. This is a descriptive study with a qualitative focus of the integrative review type, which comprises the analysis of relevant research, allowing the synthesis of information about a given context and pointing out gaps that need to be filled based on a defined and characteristic theme. Although nursing professionals understand and recognize the importance of palliative care, there is a weakened understanding, correlating them only to patients suffering from life, so professionals focus on focusing on the physical care of this patient and not on other patient needs as a singular subject. There are still difficulties in screening, prognosing, recognizing this type of patient, delaying the start of palliative care, sharing the decision-making process between a multidisciplinary team, planning care comprehensively, factors that negatively influence the achievement palliative care in the ICU.